ECG-based beat-to-beat assessment of AV node conduction properties during AF - Karlsson, Mattias; Plappert, Felix; Platonov, Pyotr G.; Östenson, Sten; Wallman, Mikael; Sandberg, Frida (Frontiers in Physiology, 2025)
IntroductionThe refractory period and conduction delay of the atrioventricular (AV) node play a crucial role in regulating the heart rate during atrial fibrillation (AF). Beat-to-beat variations in these properties are known to be induced by the autonomic nervous system (ANS) but have previously not been assessable during AF. Assessing these could provide novel information for improved diagnosis, prognosis, and treatment on an individual basis.MethodsTo estimate AV nodal conduction properties with beat-to-beat resolution, we propose a methodology comprising a network model of the AV node, a particle filter, and a smoothing algorithm. The methodology was evaluated using simulated data and using synchronized electrogram (EGM) and ECG recordings from five patients in the intracardiac atrial fibrillation database. The methodology’s ability to quantify ANS-induced changes in AV node conduction properties was evaluated by analyzing ECG data from 21 patients in AF undergoing a tilt test protocol.ResultsThe estimated refractory period and conduction delay matched the simulated ground truth based on ECG recordings with a mean absolute error (± std) of 169±14 ms for the refractory period in the fast pathway; 131±13 ms for the conduction delay in the fast pathway; 67±10 ms for the refractory period in the slow pathway; and 178±28 ms for the conduction delay in the slow pathway. These errors decreased when using simulated ground truth based on EGM recordings. Moreover, a decrease in conduction delay and refractory period in response to head-up tilt was seen during the tilt test protocol, as expected under sympathetic activation.DiscussionThese results suggest that beat-to-beat estimation of AV nodal conduction properties during AF from ECG is feasible, with different levels of uncertainty, and that the estimated properties agree with expected AV nodal modulation.